2019
DOI: 10.1038/s41598-018-36641-4
|View full text |Cite
|
Sign up to set email alerts
|

Achieving superelasticity in additively manufactured NiTi in compression without post-process heat treatment

Abstract: Shape memory alloys (SMAs), such as Nitinol (i.e., NiTi), are of great importance in biomedical and engineering applications due to their unique superelasticity and shape memory properties. In recent years, additive manufacturing (AM) processes have been used to produce complex NiTi components, which provide the ability to tailor microstructure and thus the critical properties of the alloys, such as the superelastic behavior and transformation temperatures (TTs), by selection of processing parameters. In biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(57 citation statements)
references
References 58 publications
1
45
1
Order By: Relevance
“…Wang et al [ 15 ] studied the influence of SLM parameters on the phase transition temperature of Ni-Ti alloy, and the results showed that the peak martensitic transition temperature (M P ) decreased with the increase in laser power. Moghaddam et al [ 16 ] took the scanning spacing of SLM processing parameters as the dependent variable to investigate the relationship between it and the phase transition temperature of Ni-Ti alloy. The results showed that the phase transition temperature decreased with the increase in scanning spacing.…”
Section: Ni-ti Alloys Formed By Am Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 15 ] studied the influence of SLM parameters on the phase transition temperature of Ni-Ti alloy, and the results showed that the peak martensitic transition temperature (M P ) decreased with the increase in laser power. Moghaddam et al [ 16 ] took the scanning spacing of SLM processing parameters as the dependent variable to investigate the relationship between it and the phase transition temperature of Ni-Ti alloy. The results showed that the phase transition temperature decreased with the increase in scanning spacing.…”
Section: Ni-ti Alloys Formed By Am Technologiesmentioning
confidence: 99%
“…After being held at 600 °C for 1.5 h, the sample was predeformed by 6% at room temperature and unloaded to produce 5.5% superelastic recovery, as shown in Figure 10 b. Gu et al [ 29 ] believed that increasing the volume density of laser energy could reduce the coarsened Ni 4 Ti 3 precipitates generated in situ, and significantly improved the superelastic effect of Ni-Ti alloy. Moghaddam et al [ 16 ], for the first time, used SLM technology to form a Ni-Ti alloy capable of producing 98% superelastic recovery at 5.62% predeformation without any heat treatment, which showed excellent stability, as seen in Figure 10 c,d.…”
Section: Ni-ti Alloys Formed By Am Technologiesmentioning
confidence: 99%
“…Fabrication of Ni-Ti using different additive manufacturing techniques, especially SLM [56], has been the subject of multiple studies [57]. Achieving superelasticity in Ni-Ti samples that are fabricated using SLM, usually requires a post-process heat treatment, nevertheless, a recent study has demonstrated the possibility of achieving superelasticity in as-fabricated SLM samples by adjusting the parameters of the process [58]. Thermomechanical response of additively manufactured Ni-Ti parts, including their fatigue life as well as their elastocaloric response, has been investigated and some promising results have been achieved.…”
Section: Potential Geometries Of An Active Elastocaloric Regeneratormentioning
confidence: 99%
“…ADDITIVE MANUFACTURING FROM THE POINT OF VIEW OF MATERIALS… Mechanically produced powder Ni-rich Ni-Ti alloys required aging treatment [91] Solutionized and aged Ni-Ti had a better shape memory response [92] Ni-rich Ni-Ti showed superelastic behavior [93] Shape memory effect recovery and unstable oriented/de-twinned martensite [94] NiTi50 showed excellent mechanical properties as compared to NiTi45 and NiTi55 [95] Gas atomized powder Using low scanning speed reduced the obtained shape memory effect [96] Superelastic behavior [96] Loss of nickel in the process [97] L-PBF High relative density (>97%) and hardness reported [98,99] Excellent compression fatigue resistance [100] with an irreversible stain behavior [99] Wider hatch distance decreased relative density [101] Superelastic response (95%) [102][103][104][105][106][107][108] Shape memory effect [94,105,109,110] Recovery above 5.5% [106][107][108]111] Desired stiffness was achieved by regulating the level of porosity and stiffness reduced from 69 GPa to 20.5 GPa for 58% porosity [112] Loss of nickel in the process [113,114] Wider hatch spacing led to a highly irrecoverable strain [114] Microstructure influenced the shape memory response and mechanical behavior [109,115] Martensite twins were formed easily after annealing process [116] Heat treatment above 400 °C decreased the shape recovery and transformation strain [117] Tens...…”
Section: Additive Manufacturing Of Stimuli-responsive Materialsmentioning
confidence: 99%